COMPREHENSIVE EFFORTS SEED QUALITY IMPROVEMENT OF SUGARCANE (SACCHARUMOFFICINARUM L.) THROUGH A SINGLE METHOD BUD PLANTING A GARDEN SEEDS AND PLANTING MATERIAL - Suhesti, Endang; Widaryanto, Eko; Waluyoh, Budi; Winarsih, Sri (International Journal of Research -GRANTHAALAYAH, 2018)
The study was designed to improve the quality of the SBP as milled cane planting material by improving the early growth of plants. Research carried out gradually implemented in the Indonesian Sugar Plantation Research Center (P3GI) Pasuruan, using two varieties of sugarcane are varieties Bululawang and PS 862 with numbers 7-16 buds. Germination (%), was observed on the 15th day after planting (DAP) and the growth of the plant include: plant height, number of leaves, leaf area, as well as the production of biomass include: Dry weight (DW) and fresh weight (FW) plant organs (leaves, stems, and roots). Fresh Weight (BS) and Dry Weight (BK) total crop. The results showed the top eye numbers (7,8,9,10) for both varieties provide the same germination potential (> 70%). But the number of buds bottom (11,12,13,14,15,16) Bululawang varieties give a lower percent germination than varieties of PS 862. At PS 862 varieties buds numbers 8 and 9 can generate over 95 percent germination %. Number eye affects plant growth in polybag components which include plant height, leaf area and the number of leaves and observation of the biomass production shows the influence of the number of eyes. These parameters indicate a decrease in the number and size of the eyes of the lower numbers. While the diameter rod eye development is not affected numbers. PS 862 varieties showed faster growth than Bululawang varieties. However, exposure to biomass production, Bululawang varieties showed higher yields than at PS 862 varieties.